A specific ovarian tumor protein isoform is required for efficient differentiation of germ cells in Drosophila oogenesis. - Steinhauer, W.R.; Kalfayan, L.J. (Genes & Development, 1992)
Mutations within the ovarian tumor (otu) gene result in abnormal ovarian development. It has been proposed that otu phenotypes result from abnormal germ cell division and differentiation. To understand better what role otu performs in oogenesis we have undertaken an analysis of protein expression from the otu locus. Anti-otu antibodies recognize two proteins from Drosophila ovary extracts with apparent molecular masses of 98 and 104 kD. Sequence analysis of otu cDNAs suggests that these proteins are translated from two mRNAs generated by alternative splicing of a 126-bp exon between the sixth and seventh exon of the smaller transcript. Analysis of otu protein expression in eight mutants indicates a correlation between the accumulation of the 104-kD isoform and predifferentiated germ cells and suggests that there is a developmental shift in the accumulation of the two isoforms upon differentiation of germ cells. Furthermore, the 104-kD isoform appears to be required for efficient differentiation of germ cells. Immunostaining of otu proteins is restricted to the cytoplasm of germ cells, and a rapid loss of oocyte immunostaining during stage 11 suggests that there is a rapid and selective degradation of otu proteins within the oocyte but not within its 15 interconnected nurse cells.